Tackling malnutrition in Latin America and the Caribbean: challenges and opportunities - Luis Galicia; Daniel López de Romaña; Kimberly B. Harding; Luz María De-Regil; Rubén Grajeda
ABSTRACT Undernutrition and micronutrient deficiencies are still a public health problem in Latin America and the Caribbean (LAC), and overweight and obesity have reached epidemic proportions. To assess the nutrition landscape in LAC countries and guide future nutrition efforts and investments, the Pan American Health Organization and the Micronutrient Initiative joined efforts to 1) identify information gaps and describe the current nutritional situation in the region; 2) map existing policies to address malnutrition in Latin America; 3) describe the impact of conditional cash transfer programs (CCTs) on nutrition and health outcomes; and 4) identify the challenges and opportunities to address malnutrition in the region. This article summarizes the methods and key findings from that research and describes the current challenges and opportunities in addressing malnutrition in the LAC region. LAC countries have advanced in reducing undernutrition and micronutrient deficiencies, but important gaps in information are a major concern. These countries have policies to address undernutrition and micronutrient deficiencies, but comprehensive and intersectoral policies to tackle obesity are lacking. CCTs in Brazil, Colombia, and Mexico have been reported to have a positive impact on child nutrition and health outcomes, providing an opportunity to integrate nutrition actions in intersectoral platforms. The current epidemiological situation and policy options offer an opportunity for countries, technical agencies, donors, and other stakeholders to jointly scale up nutrition actions. This can support the development of comprehensive and intersectoral policies to tackle the double burden of malnutrition, strengthen national nutrition surveillance systems, incorporate monitoring and evaluation as systematic components of policies and programs, document and increase investments in nutrition, and assess the effectiveness of such policies to support political commitment and guarantee sustainability.